STRATEGI ORGANISASI DALAM MENCAPAI KEUNGGULAN BERSAING BERKELANJUTAN: LITERATURE REVIEW - Anggitasari Anggitasari; Nugroho Yekti Utami (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The increasingly dynamic business competition requires organizations to implement strategies that enable them to achieve sustainable competitive advantage. The Resource-Based View (RBV) perspective emphasizes that competitive advantage is primarily derived from internal organizational resources rather than external market conditions. However, previous studies show varying findings regarding which RBV indicators most strongly contribute to sustainable competitive advantage. Therefore, this study aims to analyze organizational strategies in achieving sustainable competitive advantage based on the Resource-Based View through a synthesis of prior research. This study employs a literature review method by selecting open-access journal articles published between 2020 and 2025 that are relevant to RBV and competitive advantage. The selection process resulted in eight primary articles, which were analyzed using content analysis. The findings reveal that sustainable competitive advantage can be achieved when organizations simultaneously manage resources that are valuable, rare, inimitable, and non-substitutable. Moreover, the results indicate that intangible resources such as managerial capabilities, human capital, organizational culture, and specific knowledge play a dominant role in supporting organizational strategy. These findings confirm the continued relevance of the Resource-Based View as a core theoretical framework in strategic management studies and provide theoretical implications for organizations seeking to strengthen long-term competitive advantage across various sectors.